2012
DOI: 10.5923/j.env.20120203.04
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lead on Plant Growth, Lead Accumulation and Phytochelatin Contents of Hydroponically-Grown <i>Sesbania </i><i>E</i><i>xaltata</i>

Abstract: Phytoremediation is the use of living plants for the removal of contaminants from soil, water, sediments, and air. Soil contamination by heavy metals (HMs) is an important environmental concern. The success of phytoextraction, a subset of phytoremediation, as an environment clean-up technology depends on several factors including the extent of soil contamination and the bioavailability of the metal. The aim of phytoextraction research is to identify metal-tolerant plants that are capable of uptake and efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Our results showed a reduction in the growth and physiology of sunflower in lead contamination as compared to plants grown in uninoculated treatment without contamination. These findings are similar to those of Hussain et al (2006Hussain et al ( , 2013 and McComb et al (2012). It is known that the reduction in plant growth by lead contamination might be due to its interference with the uptake of nutrients, respiration, photosynthetic rate and cell membrane permeability (Sharma and Dubey 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed a reduction in the growth and physiology of sunflower in lead contamination as compared to plants grown in uninoculated treatment without contamination. These findings are similar to those of Hussain et al (2006Hussain et al ( , 2013 and McComb et al (2012). It is known that the reduction in plant growth by lead contamination might be due to its interference with the uptake of nutrients, respiration, photosynthetic rate and cell membrane permeability (Sharma and Dubey 2005).…”
Section: Discussionsupporting
confidence: 91%
“…a) might be the result of direct exposure of roots to Pb toxicity which also resulted in more pronounced activities of antioxidant enzymes in roots. An elevation in activities of antioxidative enzymes in response to Pb induced oxidative stress is well reported in literature . These enzymes serve as a prime defence strategy against radical O 2− , OH − , H 2 O 2 and conjugate dienes to prevent lipid peroxidation mediated degradation of membranes .…”
Section: Discussionmentioning
confidence: 90%
“…This might be responsible for the increase in Pb uptake with increase in Pb concentration in the present study. Many recent studies have also reported an increase in the GSH concentration with an increase in heavy metal stress due to Pb [28][29][30][31][32][33]. However, at higher concentrations of Pb, the toxicity effects also increased and reduced the Pb uptake [27].…”
Section: Effect Of Initial Heavy Metal Concentrationmentioning
confidence: 97%